Tax accounting in Ukraine - Sedlova, Anastasiya (My University, 2014)
Ukraine has two-tier tax system and levies taxes on the local and state levels. There are 18 state and 5 local taxes and charges. Ukraine imposes taxes on its residents on a worldwide basis. The residency of legal entities is determined based on the place of incorporation. As to individuals, the Tax Code provides for a tiebreaker rule.However, tax authorities tend to use the Commentaries in their interpretation of the Tax Code’s provisions.
Keywords: tax accounting; Ukraine; tax; податковий облік; Україна; податок; налоговый учет; Украина; налог